2013
DOI: 10.3846/16486897.2013.796956
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydropower dams on the state of macroinvertebrates assemblages in the Virvyte river, Lithuania

Abstract: Macroinvertebrate organization along the Virvyte ˙River was examined to relate biological response in environmental changes. Benthic macroinvertebrates and a range of environmental variables were sampled from three study sections: control, HPP dams and below HPP dams. Total macroinvertebrate taxon number (NT 28), EPT taxon number (NT 13) and Shannon-Wiener diversity index (H´3.85) were the highest in control sites of the river and the smallest in HPP dams (17, 5, 2.75, respectively). Taxon number and total abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
(44 reference statements)
3
11
0
Order By: Relevance
“…Vaikasas et al . () also found significant higher proportions of Plecoptera taxa in the control sites than in sites below hydropower dams. Reductions of Plecop_a in I A1 , I A2 , I A3 and I A4 do not seem to be related to organic pollution indeed.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Vaikasas et al . () also found significant higher proportions of Plecoptera taxa in the control sites than in sites below hydropower dams. Reductions of Plecop_a in I A1 , I A2 , I A3 and I A4 do not seem to be related to organic pollution indeed.…”
Section: Discussionmentioning
confidence: 75%
“…For example, Jones (2013) found ten times more Plecoptera in the natural rivers compared with Magpie River affected by a hydropower dam. Vaikasas et al (2013) also found significant higher proportions of Plecoptera taxa in the control sites than in sites below hydropower dams. Reductions of Plecop_a in I A1 , I A2 , I A3 and I A4 do not seem to be related to organic pollution indeed.…”
Section: Ecological Effects Of Hydrologic Alteration In the Ebro Rivementioning
confidence: 71%
See 2 more Smart Citations
“…The findings from these studies indicate that no comprehensive research on the quantification of environmental issues due to rapid HP flow fluctuations on biotic systems in Lithuanian rivers was carried out. One exception was for macro invertebrate composition [53].…”
Section: Introductionmentioning
confidence: 99%